Peran UMKM Pembuatan Makanan Ringan Dan Inovasi Produk Terhadap Penambahan Pendapatan Ekonomi Masyarakat Dikota Tangerang - Agus Suharto; Suhendri Suhendri; Berlin Berlin (Universitas Slamet Riyadi, 2022)
By the government, high attention is given to MSME actors as a form of government in supporting the economy of the small people. Moreover, MSMEs are able to have a direct impact on people's lives in the lower sector, both in rural and urban areas. Data from the Ministry of Cooperatives and SMEs in 2017 shows high foreign exchange from MSME actors. The figure is also very high, reaching Rp. 88.45 billion. This figure has increased up to eight times compared to 2016, it is not wrong if MSME actors cannot be underestimated anymore. Snacks to be sold must have good quality, both in terms of the materials used, in terms of processing and in terms of packaging. The materials used must be hygienic and do not contain harmful substances. The processing method must also be clean and guaranteed according to the rules. Then the packaging is made using good, attractive packaging and meets the brand packaging standards of the snacks. Followed by current information technology and innovation as well as good and diverse packaging so that the products we produce are more attractive to consumers or innovation in terms of marketing with online media. We see today, many snack food entrepreneurs are successful because of their innovation. Keywords : Small Micro Enterprises Manufacturing of snacks, product innovation, & community economic income.